Goodnight lab ebook A scientific parody. - Ferrie, Chris (2017)
In the vein of Goodnight Moon, say "goodnight" to your lab in this picture book parody of a beloved classic. Perfect for scientists of all ages! It's been a long day at the lab for this scientist. Now it's time to say goodnight! Goodnight laser Goodnight notebook Goodnight picture of Einstein with a stern look While poking fun at the clutter and chaos of lab life, scientists of all ages will appreciate ending their day with this sweet parody. They'll be rested and ready to return to the world of research in the morning! This scientific parody book in the style of Goodnight Moon is a delight for little lab girls and guys. Goodnight Lab is written by Chris Ferrie, author of Quantum Physics for Babies and other books in the Baby University series. Parents and kids both will love the accurate descriptions of all the quirks of grownup laboratories. Readers who love the Lab Girl book or Nerdy Babies will adore this humorous and educational book for kids. This book is the perfect solution if you're looking for science baby gifts and physics gifts for curious kids.